Pelaksanaan Pendidikan Agama Pada SMA Swasta - Wahab Wahab (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
This research is a comparative study which compared to the impact PAIprivate high school implementation islamic faundation that uses foundationand Diknas curriculum. The purpose of this study are 1) to know the differencebetween the religious behavior of students who obtain teaching religion fromdiknas curiculum and PAI foundation curicula, 2) to identify differences inreligious behavior among students of class X, XI, and XII at the PAI religious prifate high school foundation. The results showed (1) students who get educationfrom foundation curicula is better than the setudent who get education PAI from diknas curicula . 2). The student of class XII student behavior is betterthan the behavior in grade XI.